(untitled) (Ágora de Heterodoxias, 2019)
The present article has as a purpose to identify the frequency and intentions about the socially responsible behaviors, through a quantitative study that describes, relates and determines differences among the variables or factors of academic training (major attending), gender, age, socioeconomic status, term attending, and the average student achievement. For the data collection was used the Self-Attribution Questionnaire for Socially Responsible Behaviors and it was applied to a stratified sample with proportional allocation to 1090 students from Universidad Estatal de Sonora, México, distributed in 20 Academic Programs considered as a stratum. The results obtained show a higher punctuation in their media, the categories: Social coexistence (=4.1392), Academic responsibility (=4.1100) and Respect for shared spaces (=4.0465). Respecting the categories with lower punctuation in their media, in the same E1, were: Religious activities (=2.3344), Social aid (=2.6447) and Volunteer activities (=2.6940). As to E2 (intention) the higher punctuation in their media, outstand the categories: Social coexistence (=3.9814) and Respect for shared spaces (=3.8795), which indicates an intention to benefit others. The categories with lower punctuation in their media are given by the categories: Religious activities (=2.6224) and Cultural development (=2.9961). As a conclusion, it highlights that women perform a higher influence in the self-attribution for socially responsible behaviors on both scales and in each significant statistic category.